Prevalence and associated factors of parental refusal rates for routine immunisation: a cross-sectional study in Peshawar, Khyber Pakhtunkhwa, Pakistan-2024 - Muhammad Hakim; Farhad Ali; Zala; Aslam Pervaiz; Saima Afaq; Zia ul Haq (BMC Public Health)
Abstract Background Vaccine hesitancy is a serious public health problem globally, particularly in low- and middle-income countries like Pakistan. This study aims to determine the vaccination refusal rate, associated factors and perceptions of parents who refused routine immunisation within Peshawar, Khyber Pakhtunkhwa, Pakistan. Methods A cross-sectional study conducted in July-2024, among 340 parents of children aged 0–59 months. Data was collected using a structured vaccine hesitancy Survey Tool of the Strategic Advisory Group of Experts(SAGE). Multistage stratified cluster sampling was employed to ensure a representative sample of tehsils in district Peshawar. Chi-squared tests and multivariable logistic regression were used to identify factors associated with vaccine refusal. Results Among 340 participants, 22% (n = 74) refused vaccines for their children. A total of 15% employed mothers refused vaccines compared to only 4.5% unemployed mothers (p = 0.004). The highest refusal rate was in tehsil Shaheen Muslim Town where 41% of parents refused vaccination (p = 0.035). Parents who refused were less inclined to believe that vaccines protect children from vaccine preventable diseases (77% vs. 98%, p < 0.001) and expressed higher rates of vaccine hesitancy (47% vs. 29%, p = 0.003). Multivariable logistic regression revealed that employed mothers were over three times more inclined to refuse vaccination (AOR: 3.11, 95% CI: 1.25, 7.67), while factors like the total depression score was not significantly associated with refusal (p = 0.13). Barriers including distance from health facility and associated cost, (AOR: 1.82, 95% CI:1.10,3.02), and the concerns about the necessity of vaccines (AOR: 2.50, 95% CI: 1.45, 4.30) was significantly associated with vaccine refusal. Conclusions The high immunization refusal rate in Peshawar among parents was associated with maternal employment, logistical challenges such as distance immunisation services, associated cost, vaccine hesitancy and safety of vaccines. It is recommended to deploy mobile immunisation units and outreach sessions to improve access, using targeted, evidence-based education to address vaccine safety concerns.